Pressure effects on the growth of Sb2Te3 thin films processed by DC and RF sputtering - MENDOZA, ROGELIO; Sastre, Jorge; Del Oso, Alfredo; Hernández, María de los Ángeles; Lizardi, Jose; Casados, Gaspar; Santana, Guillermo (IJRDO-Journal of Applied Science, 2019)
In this work, are compare and analyze the surface structure, morphology and electrical properties of antimony telluride (Sb2Te3) thin films grown by Direct Current (DC) and Radio Frequency (RF) magnetron sputtering system, with the variation of deposit pressure (Pd) from 5 to 15 mTorr. The Sb2Te3 thin films were grown with a magnetron power of 60 W, a substrate temperature of 200 °C and deposited time of 60 minutes for all samples. Profilometry measurements, X-ray Diffraction (XRD), morphology by Scanning Electron Microscope (SEM), Energy Dispersive Spectrometry (EDS) and resistivity were carried out on the Sb2Te3 thin films. XRD results show that the Sb2Te3 thin films prepared by DC sputtering system have a higher crystalline quality respect to thin films deposited by RF sputtering and the structural properties improved by the decreasing of the deposition pressure. Morphology results revealed that when the work pressure in both sputtering systems decreased to 5 mTorr, the grains are more compacted. EDS analyses show that the atomic composition is approximately 35% at of Te and 65% at of Sb in both sputtering systems. Finally, for DC sputtering or RF sputtering systems the resistivity of the thin films decreases is close to 5.8x10-4 ohm-cm.